Soundscape planning for the Xianghe Segment of China's Grand Canal based on landsenses ecology. Issue 4 (3rd July 2016) - Dong, Rencai; Yu, Tianshu; Ma, He; Ren, Yin
ABSTRACT: Soundscape describes a sound or combination of sounds that forms or arises from an immersive environment, which plays an important role in the composition of the urban landscape. The traditional urban landscape planning and design always put weighs on the visual sense, and integrating the soundscape and visual landscape will elevate human subjective sense of the objective environment, which will promote a new view for traditional urban landscape design. In this paper, we analyzed the types and characters of acoustic environment in the Xianghe Segment of China's Grand Canal (XSCGC) based on noise monitoring data with EIoT, and proposed a model for traffic noise control to improve the acoustic environment of sensitive area such as university campus and habitations in the study area. Finally, we produced a soundscape plan based on landsenses ecology to comprehensively upgrade the quality of the soundscape in the XSCGC.